Developing local volume tables for three important tree species in Nawalparasi and Kapilvastu districts - Shrestha, H. L.; Kafle, M. R.; Khanal, K.; Mandal, R. A.; Khanal, K. (Banko Janakari, 2018)
The local volume tables of specific species are very important to estimate the timber volume of standing trees but precise site-specific volume tables are lacking for three important tree species, namely Dalbergia sissoo, Shorea robusta and Terminalia alata. Therefore, this study was carried out to develop local volume tables and determine the form factors of these species using destructive and non-destructive methods. Kapilvastu and Nawalparasi districts were selected for this study. Altogether, 188 vigorous trees were selected for measurement, out of which 156 (52 trees for each species) were from destructive sampling and 32 were standing trees. The data of destructive sampling trees of three species were used in developing the models for under bark timber volume up to 10 and 20 cm top diameters. Thirty two data (12 for S. robusta, 10 for T. alata and for D. sissoo each) of standing trees were used to validate the models of three species. A number of cross sections were made and actual volumes of stem, butt log, other sections and top portion were calculated using cylindrical, Newton’s, Smalian’s and cone formulae, respectively. The cylindrical volume was estimated based on diameter at breast height. The form factor was determined from the ratio of actual and cylindrical volumes. The diameter and height relationship was made and, based on this; the smooth curve was drawn to develop the local volume tables. The results showed that estimated form factor of 10 cm and 20 cm top diameter of selected species varied from 0.50 to 0.69. In addition, local volume tables are developed for stem volume based on diameter under bark. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 84-91